1993
DOI: 10.1172/jci116346
|View full text |Cite
|
Sign up to set email alerts
|

Role of phosphodiesterases in the regulation of endothelial permeability in vitro.

Abstract: Neutrophil-derived hydrogen peroxide (H202) is believed to play an important role in the pathogenesis of vascular injury and pulmonary edema. H202 time-and dose-dependently increased the hydraulic conductivity and decreased the selectivity of an endothelial cell monolayer derived from porcine pulmonary arteries. Effects of H202 on endothelial permeability were completely inhibited by adenylate cyclase activation with 10-12 M cholera toxin or 0.1 juM forskolin. 10' M Sp-cAMPS, a cAMP-dependent protein kinase A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
143
3

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(150 citation statements)
references
References 39 publications
4
143
3
Order By: Relevance
“…Finally, it is also possible that PDE inhibitors may be affecting the permeability of endothelial cells. Type III and IV inhibitors have been shown to reduce endothelial cell permeability in vitro (Seiburt et al, 1992;Suttorp et al, 1993) and it has been demonstrated in vivo that rolipram can inhibit PAF-induced plasma extravasation in guinea-pig airways (Raeburn & Karlsson, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is also possible that PDE inhibitors may be affecting the permeability of endothelial cells. Type III and IV inhibitors have been shown to reduce endothelial cell permeability in vitro (Seiburt et al, 1992;Suttorp et al, 1993) and it has been demonstrated in vivo that rolipram can inhibit PAF-induced plasma extravasation in guinea-pig airways (Raeburn & Karlsson, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…5,9,11 Exposure of endothelial cells to hydrogen peroxide (H 2 O 2 ) results in the activation of multiple signaling pathways, finally leading to the activation of myosin light chain (MLC) kinase and disrupted barrier function. 7,8 Thrombin-activated Rho kinase increases the phosphorylation of endothelial cell MLC by directly phosphorylating MLC and simultaneously inhibiting MLC phosphatase, thereby maximally enhancing MLC phosphorylation. 4,5 The hemolysin of Escherichia coli (HlyA) is an important prototype of pore-forming bacterial exotoxins that allows Ca 2ϩ influx into the cytosol of target cells.…”
Section: ;91:618-625)mentioning
confidence: 99%
“…2,8,9,14 Analysis of the endothelial cell PDE isoenzyme pattern showed high activities of PDE2 to PDE4. PDE2 mainly metabolizes cGMP, whereas PDE3/4 is specific for cAMP.…”
Section: ;91:618-625)mentioning
confidence: 99%
See 1 more Smart Citation
“…(14,15) Prostaglandins, such as PGE 1 and PGI 2 , are potent vasodilators that are generally administered directly to the pulmonary circulation at the time of graft perfusion and are added to the hypothermic preservation solution. The beneficial effect of prostaglandins on lung transplantation is related to the preservation of the endothelial barrier of the pulmonary vasculature (16) and to vasodilation, which facilitates the distribution of the preservation solution through the lung parenchyma at extraction. Intracellular solutions, such as the Euro-Collins and University of Wisconsin solutions, have a high potassium content, which causes pulmonary vasoconstriction, vasodilators being therefore required during the administrations of such solutions.…”
Section: Discussionmentioning
confidence: 99%